Odpowiedzi

2010-03-02T19:25:35+01:00
A=3 b=x c=pierw z 13

3² +x² = pier z 13 ²
9+x² =13
x² =4
x=2

a=3pier.3 b=2pier. 5 c=x

a² + b² =c²
27+20=x²
47=x²
x= pierwiastek z 47
1 5 1
2010-03-02T19:25:47+01:00
A=3
b=x
c=√13

3² + x² = (√13)²
9 + x² = 13
x² = 4
x = 2

a=3√3
b=2√5
c=x

(3√3)² + (2√5)² = x²
27 + 20 = x²
x² = 47
x = √47

Pozdrawiam :*
1 5 1
2010-03-02T19:26:51+01:00
3kw + x kw = √13kw
9 + x kw = 13 /-9
x kw = 4/pierwiastkujemy
x = √4
x = 2

3√3 kw + 2√5 kw = x kw
√27 kw + √20 kw = x kw
27 + 20 = x kw
47 = xkw/pierwistkujemy
√47 = x

kw to kwadrat bo mi nie wyskakuje :)
1 5 1